The Use of FTIR and Micro-FTIR Spectroscopy: An Example of Application to Cultural Heritage. (10th May 2009) - La Russa, Mauro Francesco; Ruffolo, Silvestro Antonio; Barone, Germana; Crisci, Gino Mirocle; Mazzoleni, Paolo; Pezzino, Antonino
Abstract : Micro-FTIR and FTIR spectroscopy is useful for the study of degradation forms of cultural heritage. In particular it permits to identify the degradation phases and to establish the structural relationship between them and the substratum. In this paper, we report the results obtained on marble from a Roman sarcophagus, located in the medieval cloister of St. Cosimato Convent (Rome), and on oolitic limestone from the facade of St. Giuseppe Church in Syracuse (Sicily). The main components found in the samples of both monuments are: gypsum, calcium oxalate, and organic matter due to probably conservation treatments. In particular, the qualitative distribution maps of degradation products, obtained by means of micro-FTIR operating in ATR mode, revealed that the degradation process is present deep inside the stones also if it is not visible macroscopically. This process represents the main cause of crumbling of the substrate. The results of this research highlight the benefits of theμ -FTIR analysis providing useful insights on the polishing and consolidation processes of stone materials.